Penyuluhan Kesehatan Tentang Pemeriksaan Tuberkulosis di RSUP H. Adam Malik Medan - Perry Boy Chandra Siahaan; Firman Firdauz Saputra; Mardi Fadillah; Onetusfifsi Putra; Eva Flourentina Kusumawardani; Meutia Paradhiba; Rubi Rimonda (PT.Mantaya Idea Batara, 2022)
Bacterium Mycobacterium tuberculosis is the cause of the infectious disease Tuberculosis. In adults, it is estimated that there are 2 million deaths every year, so that tuberculosis is the most infectious disease in the world. Factors that cause a person to get TB, namely when the immune system decreases and other supporting factors such as age, education level, smoking, alcohol, malnutrition, diabetes, and adherence to treatment, based on the service team, It is known that knowledge about how to prevent and treat Tuberculosis Disease is less known by patients and families. so that counseling is important to be held at H. Adam Malik Hospital Medan because it is a problem encountered by partners. This counseling was held at H. Adam Malik Hospital, Medan. The method in this service is carried out through questions and answers, discussions and lectures/counseling, The results we obtained were that the patient and patient's family were active and enthusiastic patients and their families to ask questions so they are committed to maintaining cleanliness, maintaining sanitation hygiene, and being obedient to taking medication completely increased and their knowledge will increase about Tuberculosis.